The 25 sitcoms that changed television : turning points in American culture - Westengard, Laura; Barlow, Aaron, 1951- (Praeger, 2018)
This book spotlights the 25 most important sitcoms to ever air on American television--shows that made generations laugh, challenged our ideas regarding gender, family, race, marital roles, and sexual identity, and now serve as time capsules of U.S. history. -- Provided by publisher.